The glycolytic enzyme, GPI, is a functionally conserved modifier of dopaminergic neurodegeneration in Parkinson's models. - Knight, A.L.; Yan, X.; Hamamichi, S.; Ajjuri, R.R.; Mazzulli, J.R.; Zhang, M.W.; Daigle, J.G.; Zhang, S.; Borom, A.R.; Roberts, L.R.; Lee, S.K.; DeLeon, S.M.; et al. (Cell Metabolism, 2014)
Neurodegenerative diseases represent an increasing burden in our aging society, yet the underlying metabolic factors influencing onset and progression remain poorly defined. The relationship between impaired IGF-1/insulin-like signaling (IIS) and lifespan extension represents an opportunity to investigate the interface of metabolism with age-associated neurodegeneration. Using data sets of established DAF-2/IIS-signaling components in Caenorhabditis elegans, we conducted systematic RNAi screens in worms to select for daf-2-associated genetic modifiers of ?-synuclein misfolding and dopaminergic neurodegeneration, two clinical hallmarks of Parkinson's disease. An outcome of this strategy was the identification of GPI-1/GPI, an enzyme in glucose metabolism, as a daf-2-regulated modifier that acts independent of the downstream cytoprotective transcription factor DAF-16/FOXO to modulate neuroprotection. Subsequent mechanistic analyses using Drosophila and mouse primary neuron cultures further validated the conserved nature of GPI neuroprotection from ?-synuclein proteotoxicity. Collectively, these results support glucose metabolism as a conserved functional node at the intersection of proteostasis and neurodegeneration.